Treatments for early-stage Dupuytren’s disease: an evidence-based approach - Nanchahal, J; Chan, JK-K (SAGE Publications, 2023)
Current treatments for Dupuytren’s disease are limited to late-stage disease when patients have developed flexion contractures and have impaired hand function. They all have limitations, including the risk of recurrence and complications. The use of treatments for early-stage disease, such as intralesional steroid injections or radiotherapy which lack a clear biological basis or evidence of effectiveness based robust randomized, double blind, placebo-controlled trials, highlights the desire of patients to access treatments before they develop significant flexion contractures. A detailed understanding of the cellular landscape and molecular signalling in nodules of early-stage disease would permit the identification of potential therapeutic targets. This approach led to the identification of tumour necrosis factor (TNF) as a target. A phase 2a clinical trial identified 40 mg in 0.4 mL adalimumab as the most efficacious dose and a subsequent randomized, double blind, placebo-controlled phase 2b trial showed that four intranodular injections at 3-month intervals resulted in decrease in nodule hardness and size on ultrasound scan at 12 months, and both parameters continued to decrease further at 18 months, 9 months after the final injection. This type of approach provides clinicians with a robust evidence base for advising their patients.